Unified in a Conflict, Moros y Cristianos and Moreska, Mimetic Fascination of Intercultural Agon - Čale-Feldman, Lada (Array, 2003)
The narrative of the battle between Moros and Cristianos is still alive in modern Spain, giving rise to numerous and diverse ritualized practices, from street performances to danced mock-battles. Its various echoes throughout Europe have been thoroughly studied, including the moreška, a dramatized dance performed on the island of Korcula, the only surviving example of the Moros y Cristianos theme still performed in Europe outside Spain. The aim of the paper, however, is not to trace the origin of the Croatian dance and the foundation of this lasting Spanish "influence", but to address a more general issue regarding the fascination of the whole family of European, mostly Mediterranean performances, with a conflict which was historically characteristic only of Spain, but whose fictional elaborations earned it the status of an obsessive mirror of recognition. This fictional, mimetic "conviviality in conflict" will be interpreted as a shared fascination with the battle of the Self with its internal Other. The analysis will refer to René Girard's theory of agonal mimetism, its further elaborations in the work of Eric Gans, and Eve Kosofsky Sedgwick's gender-sensitive critique, since the figure most often disregarded in the interpretations of the theme is a female character in whose name or in whose favor the battle is taking place.